Ecological and hygienic determination of the deterioration of population’s health in the industrial region - Bіletska, E.M.; Onul, N.M.; Holovkova, T.A.; Antonova, O.V.; Zemliakova, T.D. (Environment & Health, 2016)
On the basis of the results of more than 20-years research, performed in the Department of General Hygiene of the Dnipro Medical Academy, we revealed a considerable technogenic load with xenobiotics on the organism of the person who lived under conditions of the industrial territories and excess of the level of xenobiotics’ content in the biological substrates of 1,6-5,0 times in "mother-fetus-child" system in comparison with a standard level. At the same time an excessive content of xenobiotics in the organism combines with a deficiency of the essential microelements, it forms a doubly unfavorable situation for the population’s health and underlines a potential danger even for small concentrations of toxicants in the environment.Such a negative state of the population’s health in the Dnipro region scientifically substantiates a necessity of the urgent introduction of socio-economic, organizational and medical-preventive measures at national level which are based on the conceptual model of risk management of the ecologically induced pathology development in the population of the industrial region.
Keywords: technogenic contamination; microelements; heavy metals; health; critical groups of population; impact